Effect of The Addition of Whey Protein-Basil Seed Gum on The Quality, Properties, and Antioxidant Activities of Low-Fat Mayonnaise: Manufacture of low-fat mayonnaise using whey protein-basil seed gum - Kim, Young-soon; Kim, Si Yeon; bin O, Hyeon; Lee, Phyrim (Progress in Nutrition, 2021)
In this study, our aim was to develop 50% fat reduced mayonnaise using whey protein isolate (5%) -basil seed gum (BSG) complex, and analyze its physicochemical, storage stability and sensory evaluation. Five different samples were prepared with different concentration of BSG complexes (0 %, 0.2%, 0.4%, 0.6% and 0.8%). The pH and viscosity increased significantly with increasing concentration of basil seed gum complexes(p<0.001). The L-value decreased, while the a-value and b-value were slightly increased (p<0.001). As the viscosity increased, the gel strength, hardness, and cohesiveness also increased (p<0.001). The oil separation, emulsion stability and freeze-thaw stability were measured during 16 days. The increase in the total phenol and flavonoid content, and ferric ion reducing antioxidant power (FRAP) with the increase in BSG of complexes increase the antioxidant activities. The sensory evaluation showed no significant difference between the samples except appearance(p<0.001).